Antimicrobial effect of active carbonaceous material obtained by hydrothermal carbonization of fructose - Branka Kaluđerović; Vesna Mandušić; Đuro Čokeša; Vladimir Dodevski; Sanja Krstić; Jelena Hranisavljević; Srđan Milanović (Zaštita Materijala)
Activated carbons due to their antimicrobial effect have been used in medicine for a long period of time. The active carbon material is obtained at a temperature of 260°C, by hydrothermal carbonization of fructose in the presence of phosphoric acid. The resulting carbonaceous materials were characterized by: nitrogen adsorption/desorption isotherms measurements, by scanning electron microscope and Fourier transform infrared spectroscopy. The resulting material was examined as an antimicrobial agent by using LB agar assay on skin microbes. The obtained active carbon material has a specific surface area of 932 m2/g. The presence of oxygen functional groups on the material surface was observed and material was proved to be a very good antimicrobial agent. The concentration of activated carbon strongly affects antimicrobial effects.